Nursing courses concerning the national curriculum guidelines: an integrative literature review Cursos de enfermería con vistas a los lineamientos - Iacida Soriano, Elaine Cristina; Biffe Peres, Cássia Regina; Sanches Marin, Maria José; da Rocha Tonhom, Silvia Franco (Revista de Enfermagem UFPE on line, 2015)
Objective: to analyze how curriculum changes have been occurring in different nursing courses. Method: An integrative review research conducted according to the Latin American Literature System on Health Sciences, using the descriptors : " Curriculum and Nursing " in the period from 2005-2013 , 251 publications have been obtained, being excluded the ones that had no direct relations with the National Curriculum Guidelines of Nursing , leaving 25 articles. Results: 84% of the studies were conducted in public institutions and 60% of them in the south and southeast of the country. Three categories have been generated: "The collective construction of pedagogical course projects," "The curriculum construction permeated by the principles and guidelines of the NHS and by new approaches in the learning process " and " Challenges of curriculum construction in accordance to the National Curriculum Guidelines ." Conclusion: some institutions have been seekingnot only curriculum changes but also some transformation in the teaching and learning processes, making use of the dialogic processes. In others, the difficulties begin in the structural bases.